Micro-Raman Spectroscopy Analysis of Optically Trapped Erythrocytes in Jaundice - Jacob, Sanu Susan; Bankapur, Aseefhali; Barkur, Surekha; Acharya, Mahendra; Chidangil, Santhosh; Rao, Pragna; Kamath, Asha; Lakshmi, R. Vani; Baby, Prathap M.; Rao, Raghavendra K. (Frontiers in Physiology, 2020)
Derangements in bilirubin metabolism and/or dysfunctions in the hepato-biliary system lead to the unhealthy buildup of bilirubin in blood, resulting in jaundice. During the course of this disorder, circulating red cells are invariably subjected to toxic effects of serum bilirubin and an array of inflammatory compounds. This study aimed to investigate the vibrational spectroscopy of live red cells in jaundice using micro-Raman spectroscopy combined with optical-trap. Red cells from blood samples of healthy volunteers and patients with jaundice were optically immobilized and micro-Raman probed using a 785 nm diode laser. Raman signatures from red cells in jaundice exhibited significant variations from the normal and the spectral-markers were obtained from multivariate analytical methods. This research gives insightful views on how different pathologies can act as ‘stress-milieus’ for red cells in circulation, possibly impeding their normal functions and also exasperating anemia. Raman spectroscopy, an emerging bio-analytical technique, is sensitive in detecting molecular-conformations in situ, at cellular-levels and in real-time. This study could pave way in understanding fundamental red cell behavior in different diseases by analyzing Raman markers.